Characterization of the human 5-lipoxygenase gene. - Funk, C D (1989)
The gene for human 5-lipoxygenase has been isolated from three different bacteriophage genomic libraries and a genomic cosmid library. The gene spans greater than 82 kilobases and consists of 14 exons. The size range for the exons is 82-613 base pairs, whereas that for the introns is approximately 200 bp to greater than 26 kb. A major site of transcription initiation in leukocytes was mapped to a thymidine residue 65 base pairs upstream of the ATG initiation codon by nuclease S1 protection and primer extension experiments. Other potential minor initiation sites were found. The putative promoter region contains no TATA and CCAAT sequences in the expected positions upstream of the major transcription initiation site but contains multiple GC boxes within a (G + C)-rich region, as does the immediate 5' region of the first intron. Characteristics common to the 5' end of the human 5-lipoxygenase gene and the promoter regions of the housekeeping genes raise important questions concerning the regulation of 5-lipoxygenase gene expression.